DEVELOPING INTENSIVE READING MATERIALS INTEGRATED WITH ISLAMIC VALUES FOR SHARIA FACULTY STUDENTS - Yuni Amelia; Prisna Aswarita Putri (Universitas Darussalam Gontor, 2026)
The absence of contextually relevant English intensive reading materials for Islamic law students in Indonesian Islamic universities represents a significant pedagogical gap. This study aimed to develop ESP intensive reading materials integrated with Islamic values for first-year students at the Faculty of Sharia, UIN Datokarama Palu. Employing a Research and Development (R&D) design based on the 4D model (Define, Design, Develop), this study involved first-year students from four departments: Family Law, Islamic Economic Law, Comparative Madhab, and Islamic Constitutional Law, whose English proficiency was identified at CEFR A1–A2 level. A needs analysis was conducted through observation, document review, and lecturer interviews, revealing the absence of discipline-specific reading materials within the faculty. Based on these findings, six reading units were developed covering core Islamic law topics: Fiqh Ibadah, Muamalah, Zakat, Munakahat, Mawarish, and Wakaf. The developed materials were validated by three experts, two Islamic Law experts and one ESP/language expert, with an overall validation score of 94.55%, categorized as Very Valid. The findings confirm that needs-based, context-specific ESP materials integrating Islamic values are both feasible and pedagogically appropriate for Sharia Faculty EFL learners.